Gallbladder-preserving polypectomy for gallbladder polyp by embryonic-natural orifice transumbilical endoscopic surgery with a gastric endoscopy - Xiao-Jian He (BMC Gastroenterology, 2022)
Abstract Background and aims Cholecystectomy is performed for most gallbladder polyps (GPs). However, cholecystectomy results concerning complications in some patients. For benign GPs, adoption of gallbladder-preserving surgery is worth to recommend. We describe our experiences performing gallbladder-preserving polypectomy for GPs by embryonic-natural orifice transumbilical endoscopic surgery (E-NOTES) with a gastric endoscopy. Methods This is a retrospective study of patients with GPs who underwent gallbladder-preserving polypectomy by E-NOTES with a gastric endoscopy from April 2018 to September 2019 in our hospital. The operative time, intraoperative hemorrhage, intraoperative and postoperative complications, gallbladder emptying function were obtained and analyzed. Results The procedure was performed successfully in all 12 patients with 5 cases of single polyp and 7 cases of multiple polyps. The range of GPs size was 2 mm to 15 mm. The mean operation time was (95.33 ± 23.08) minutes (55–135 min). There were no adverse events including heavy bleeding, mortality and conversion to open surgery during operation. All patients were discharged in 4–5 days after surgery without postoperative complications such as delayed bleeding, fever, peritonitis, intra-abdominal abscess and abdominal wall incisional hernia. All patients were followed up at 1, 3, 6, and 12 months postoperation who had almost no visible incision on the umbilical region, no recurrent GPs. The gallbladder emptying function decreased one month after surgery, and gradually improved 3, 6 and 12 months after surgery. Conclusion E-NOTES gallbladder-preserving polypectomy is a safe and effective option for patients with GPs and is close to scar-free surgery which can be performed in routine clinical practice.